Movie Magic! / Maizura Manshor and Efina Hamdan - Manshor, Maizura; Hamdan, Efina (Universiti Teknologi MARA, Negeri Sembilan, 2024)
In our fast-paced world, finding ways to unwind from work is crucial, and movies offer one of the most enjoyable escapes. From a media behavioural perspective, watching films can significantly reduce stress and enhance our well- being by providing a temporary but effective mental getaway. Movies are a powerful form of escapism because they transport us to different worlds and stories. Think about delving into the intense horror elements in “Pulau”, exploring the vibrant romantic comedy in “La Luna”, or experiencing the emotional depth of “172 Days”. These experiences let us step away from our daily work routine and immerse ourselves in captivating narratives, offering a refreshing mental break. The sensory engagement of movies plays a crucial role in their ability to help us escape. The stunning visuals, dynamic soundtracks, and compelling storylines capture our attention and divert our focus from work stress. This immersive experience engages multiple parts of our brain, creating a holistic distraction that allows us to relax and recharge.